Congenital NOS2 deficiency protects mice from LPS-induced hyporesponsiveness to inhaled nitric oxide - Weimann, Jörg; Bloch, Kenneth D.; Takata, Masao; Steudel, Wolfgang; Zapol, Warren M. (Anesthesiology, 1999)
BACKGROUND: In animal models, endotoxin (lipopolysaccharide) challenge impairs the pulmonary vasodilator response to inhaled nitric oxide (NO). This impairment is prevented by treatment with inhibitors of NO synthase 2 (NOS2), including glucocorticoids and L-arginine analogs. However, because these inhibitors are not specific for NOS2, the role of this enzyme in the impairment of NO responsiveness by lipopolysaccharide remains incompletely defined. METHODS: To investigate the role of NOS2 in the development of lipopolysaccharide-induced impairment of NO responsiveness, the authors measured the vasodilator response to inhalation of 0.4, 4, and 40 ppm NO in isolated, perfused, and ventilated lungs obtained from lipopolysaccharide-pretreated (50 mg/kg intraperitoneally 16 h before lung perfusion) and untreated wild-type and NOS2-deficient mice. The authors also evaluated the effects of breathing NO for 16 h on pulmonary vascular responsiveness during subsequent ventilation with NO. RESULTS: In wild-type mice, lipopolysaccharide challenge impaired the pulmonary vasodilator response to 0.4 and 4 ppm NO (reduced 79% and 45%, respectively, P < 0.001), but not to 40 ppm. In contrast, lipopolysaccharide administration did not impair the vasodilator response to inhaled NO in NOS2-deficient mice. Breathing 20 ppm NO for 16 h decreased the vasodilator response to subsequent ventilation with NO in lipopolysaccharide-pretreated NOS2-deficient mice, but not in lipopolysaccharide-pretreated wild-type, untreated NOS2-deficient or untreated wild-type mice. CONCLUSIONS: In response to endotoxin challenge, NO, either endogenously produced by NOS2 in wild-type mice or added to the air inhaled by NOS2-deficient mice, is necessary to impair vascular responsiveness to inhaled NO. Prolonged NO breathing, without endotoxin, does not impair vasodilation in response to subsequent NO inhalation. These results suggest that NO, plus other lipopolysaccharide-induced products, are necessary to impair responsiveness to inhaled NO in a murine sepsis model.